The Effect of Decoction of Coriander Seeds on Blood Pressure in Menopausal Women with Hypertension in the Work Area of the Mrican Health Center Kediri in 2022 - Betanuari Sabda Nirwana; Eva Dianingtyas Ariyanti; Gilang Dewanti Harimurti; Hendargo Agung Pribadi; Khofidhotur Rofiah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
This study is based on the high incidence of hypertension in menopausal women and 40% of them solved it by consuming herbal drinking from their parents before. One of the herbs that can be used to lower blood pressure is coriander seeds. The purpose of this study is the influence of coriander seed stew to the blood pressure of menopausal women who experience hypertension in the work area of ​​Mrican Public Health Center Kediri in 2022. The design used in this research is pre experimental with pretest-post test one group design approach. The population in this study were all postmenopausal women who experienced hypertension in Gayam Posyandu village 3 working area of ​​Mrican Kediri Public Health Center in April 2022 of 27 people. Sampling technique of this research is purposive sampling. The sample size is 20 people. The independent variable (X) in this research is coriander seed stew while blood pressure as dependent variable (Y). The instrument used is spygmo manometer. Data analysis using T paired samples. The results showed that the mean blood pressure value of sistole after giving the coriander seed stew was lower than before, as was the diastolic blood pressure. Result of data analysis got pvalue = 0.000 or less from α = 0,05 meaning that H0 rejected and H1 accepted, meaning there is influence of coriander seed stew to blood pressure of menopausal women who have hypertension in Work Area of ​​Mrican Kediri Public Health Center in 2022. Coriander seeds can lower blood pressure elderly because it contains flavonoids. Elderly are expected to consume coriander seed stew regularly because hypertension is a chronic disease, control blood pressure to the health center on a regular basis.